THE INFLUENCE OF EMERGING TECHNOLOGIES ON COMMUNICATION PRACTICES IN THE DIGITAL AGE - Musawer Hakimi; Ahmad Jamy Kohistani; Abdul Shakoor Azimy; I Made Ardi Sudestra (Jurnal Ilmiah Dinamika Sosial)
The speed with which emerging digital technologies have changed our communications has impacted many aspects of the communication process wherever people interact in their personal and professional lives. In part this study sought to explore the influence of emerging digital communication technologies on users’ communication behaviors, perceptions and attitudes. A quantitative research design was used. Data was collected online through an online survey. We collected data from 278 participants age 18 years and older. Stratified random sampling was used to provide an adequate demographic representation. The instrument consisted of demographic items, technology use patterns and Likert-style questions to depict users’ perception of if their communication changed and about their attitude toward technology.  Descriptive statistics indicated very high use rates of e-mail (89.3%), AI (86.5%) and video conferencing (84.0%). While technology use varied daily, 27.3% of participants indicated they spent more than five hours each day communicating digitally. When user perceptions associated with technology impacts were reported as moderate agreements that the emerging technologies improved the speed and access of communication; however, concussions about the quality of the interaction that replaced face-to-face time was are something to think about. We'd like to point out that the overall reliability of the survey instrument was reasonable69 for a couple of key sections, Cronbach's alpha was above 0.7. The initial findings of this research indicate that while emerging digital technologies have improved the speed of connection and efficiency in communication, users are still careful of the social ramifications. Future discussions and strategies should look to balance technological gains and the need for some form of inter-personal relationship. This research is a contribution to the literature for research and practice, especially as it relates to the burgeoning evolution of digital communications.